Assessment of appendix carcinoid tumors: A retrospective study - Servet Kocaoz; Gulay Turan (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aimed to analyze the frequency of carcinoid tumor, the applied treatments to cure it, and the survival periods of the patients thereafter in a city located in the west of Turkey, Balıkesir. Materials and Methods: The data for this study were gathered by the careful retrospective analysis of 6369 files of patients who underwent an appendectomy operation during the time span of January 2011 and December 2017 in Balıkesir Atatürk City Hospital. Results: The results revealed that among the patients who underwent appendectomy, 17 carcinoid tumor cases, 16 of which with combine classic carcinoid and 1 with goblet cell carcinoid, were recorded. It was discovered that about two times more carcinoid tumors were found in females compared to males. It was also revealed that in the 14 (82.4%) of the patients, the diameter of the tumor was <1 cm. Since the diameter of the tumor is <2 cm in classic carcinoid cases, these patients were only observed. Moreover, within the 5-year follow-up period, no recurrence or progress of carcinoid syndrome was detected. Furthermore, this study found out that the 5-year-survival rate of all the carcinoid tumor patients involved in the study was 100%. Conclusions: It is highly important that the histopathological diagnosis of the patients after appendectomy be carefully followed as the appendicitis carcinoid tumors which are encountered more commonly in women than in men are asymptomatic and can only be incidentally detected.